Kamusku Application as a Media in Reading Online English News - Ari Astutik; Yulis Setyowati (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
This study aims to find out the students’ perceptions in using the application of the English Dictionary "Kamusku" as a media in reading online English news can make them feel more easier in learning vocabulary and understand the English online news well. This study uses a qualitative study with open ended questionnaires, The instruments used in this method are questionnaires question. This research was conducted on first semester students of English Literature at Wijaya Putra University. The results of the study obtained that the application of the English Dictionary "Kamusku" as a media in reading Online English News had a positive and significant effect on increasing students' English vocabulary to comprehend in reading the online English News.